2021
DOI: 10.1097/jxx.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic simulations in nurse practitioner education: Improving skin cancer knowledge, confidence, and performance

Abstract: Background: The rising incidence of skin cancer continues to be a significant public health concern in the United States. Nurse practitioners (NPs) have a key role in early detection of skin cancer. However, NP students currently demonstrate low levels of knowledge related to skin cancer assessments and recognition of skin lesions.Purpose: The aim of this pilot study was to determine if simulations with standardized patients wearing threedimensional (3D) prosthetic skin lesions improved NP students' knowledge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…In a review of the literature, no articles were identified that evaluated NNPs' performance of caring for infants with fragile skin. Authors of a recent study of family NPs and adult-gerontology acute care NPs found that simulation with standardized patients enhanced NP students' knowledge, self-confidence, and performance of skin cancer assessments 17. Similar to the findings from Shue-McGuffin and Powers,17 participants in this project reported high levels of satisfaction with the learning experience.…”
Section: Discussionsupporting
confidence: 67%
“…In a review of the literature, no articles were identified that evaluated NNPs' performance of caring for infants with fragile skin. Authors of a recent study of family NPs and adult-gerontology acute care NPs found that simulation with standardized patients enhanced NP students' knowledge, self-confidence, and performance of skin cancer assessments 17. Similar to the findings from Shue-McGuffin and Powers,17 participants in this project reported high levels of satisfaction with the learning experience.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have concluded that education can improve nurse practitioners' knowledge and behaviors to identify skin cancer (Goodman, 2016; Hartnett & O'Keefe, 2016). In addition, a study by Shue-McGuffin and Powers (2021) found that an educational intervention to identify skin lesions increased student nurse practitioners' knowledge and self-confidence to detect skin cancer.…”
Section: Resultsmentioning
confidence: 99%
“…To maximize ability to detect abnormal lesions and educate patients, programs can utilize simulations of dermatologic examinations in addition to didactic teaching (Wingo & Baker, 2018). Research has shown practice educating patients on prevention strategies through use of standardized patients can improve nurse practitioner students' knowledge and confidence (Shue-McGuffin & Powers, 2022). Undergraduate and graduate nursing students should also be instructed to incorporate skin assessments and sun safety education into every clinical learning experience to reinforce integration of this vital aspect of patient care into their practice.…”
Section: Additional Recommendationsmentioning
confidence: 99%
“…Undergraduate and graduate nursing students should also be instructed to incorporate skin assessments and sun safety education into every clinical learning experience to reinforce integration of this vital aspect of patient care into their practice. This simulation and clinical experiential learning should include performing proper skin assessments on diverse individuals to ensure students are prepared to provide this needed care to all patients (Shue-McGuffin & Powers, 2022; Woodmansee et al, 2018). In addition, continuing education is important as research with practicing nurse practitioners has shown a lack of skin cancer knowledge and desire for more education on melanoma (Roebuck et al, 2015).…”
Section: Additional Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation